Enacted Faith, Youth Ministry and Theological Shorthand - Bailey, David (Journal of youth and theology, 2014)
Theological shorthand is expressed through the words: relationships, like Jesus, being there, and time and journey. These words articulate a complex and nuanced practice that carry and communicate the Gospel and faith of youth ministers amongst young people. When examined, the practice of youth ministers resonate with echoes of theology from the Christian tradition, yet this is not overtly expressed. The theological shorthand articulation can be seen as ‘thin’ theology, with practice based on being like Jesus and the youth minister as symbol. Current youth ministry practice can be seen to be guided by the normative voice of the literature on youth ministry. Through these, practice has the potential to be limited theologically and risks un-tethering youth ministry from the church and wider Christian tradition.